International student exchange and academic performance - Dirk Czarnitzki; Wytse Joosten; Otto Toivanen (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2021)
International student exchange has become an important part of university-level studies and the EU plans to increase it significantly. We analyze how international student exchange affects students' academic human capital. Using detailed student-level data from four faculties (Economics and Business, Law, Engineering and Science) of a large Belgian public university we find that, on average, exchange students lose 7% in terms of grades relative to their non-mobile peers, but less so in Erasmus-facilitated exchange. Since students' academic performance is an important factor in companies' hiring decisions, participation in international exchange seems to have a non-negligible impact on labor market outcomes.
Keywords: I23; I26; J24; 330; Exchange programs; student mobility; academic performance